1999
DOI: 10.1046/j.1365-2249.1999.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative differences in bronchoalveolar inflammatory cells inPseudomonas aeruginosa-resistant and -susceptible mice

Abstract: SUMMARYThe difference in severity of Pseudomonas aeruginosa-induced chronic lung infection may be determined by differences in host in¯ammatory responses. In the present study we investigate this possibility using BALB/c and C57Bl/6 mice, resistant and susceptible, respectively, to chronic lung infection with P. aeruginosa. Following intratracheal inoculation of P. aeruginosa-impregnated agar beads, C57Bl/6 mice mounted a stronger in¯ammatory response with signi®cantly higher total cell numbers in the bronchoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
8
34
0
Order By: Relevance
“…5). TNF-␣ is a critical cytokine for the elimination of P. aeruginosa (19,20). Previous data have demonstrated that the immunosuppression associated with cecal ligation and puncture (CLP) models of sepsis is associated with defective production of TNF-␣ by AMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). TNF-␣ is a critical cytokine for the elimination of P. aeruginosa (19,20). Previous data have demonstrated that the immunosuppression associated with cecal ligation and puncture (CLP) models of sepsis is associated with defective production of TNF-␣ by AMs.…”
Section: Discussionmentioning
confidence: 99%
“…The transient transgenic expression of TNF-␣ within the lungs of CLP animals improves AM phagocytic function and protects from P. aeruginosa infection (19,20). Further experimental evidence for the importance of AMs and TNF-␣ production in the clearance of P. aeruginosa come from studies examining chronic P. aeruginosa infection in resistant (BALB/c) vs susceptible (C57BL/6) strains of mice (19,20). These experiments demonstrated that TNF-␣ production by AMs was significantly higher in resistant BALB/c mice on day 7 postinfection than in susceptible C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-CF mice, infection with P. aeruginosa-laden beads can persist for up to 28 days, 22,46,47 whereas CFTR knockout mice appear to have more severe mortality and inflammation, characterized by high levels of proinflammatory mediators (TNF-a, KC and MIP-2) 3 days after exposure to the beads. Between days 3 and 7 after infection with P. aeruginosa-laden beads in CF mice, the process of bacterial killing is Figure 4 Inflammation-associated pathology is reduced in AAV5.Cb-mIL10-treated mice.…”
Section: Il-mentioning
confidence: 99%
“…However, Oc formation in this study occurred only in Balb/c and not C57BL/ 6 mice, the animals used in our study. Previous studies have demonstrated that Balb/c and C57BL/6 mice mount different responses to inflammatory stimuli (Sapru et al 1999). Such differences likely contributed to these conflicting results.…”
Section: Figmentioning
confidence: 99%